2015
DOI: 10.3389/fmicb.2015.00944
|View full text |Cite
|
Sign up to set email alerts
|

Geriatric Respondents and Non-Respondents to Probiotic Intervention Can be Differentiated by Inherent Gut Microbiome Composition

Abstract: ScopeProbiotic interventions are known to have been shown to influence the composition of the intestinal microbiota in geriatrics. The growing concern is the apparent variation in response to identical strain dosage among human volunteers. One factor that governs this variation is the host gut microbiome. In this study, we attempted to define a core gut metagenome, which could act as a predisposition signature marker of inherent bacterial community that can help predict the success of a probiotic intervention.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 71 publications
1
11
0
Order By: Relevance
“…Additionally, studies that have measured changes in performance in response to probiotic supplementation have not looked at individual's gut microbiota composition directly. This is a limitation of these studies as different strains of probiotic bacteria show differing rates of survival through the gastrointestinal tract (157) and the composition of an individual's gut microbiota may also influence the persistence and function of probiotic bacteria in the gut (158)(159)(160). Therefore, not all probiotic strains may survive in sufficient quantities to make it down to the gut microbiome and, even if the probiotic bacteria reach the gut microbiome, it may not last as long or have the same effect in each individual.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, studies that have measured changes in performance in response to probiotic supplementation have not looked at individual's gut microbiota composition directly. This is a limitation of these studies as different strains of probiotic bacteria show differing rates of survival through the gastrointestinal tract (157) and the composition of an individual's gut microbiota may also influence the persistence and function of probiotic bacteria in the gut (158)(159)(160). Therefore, not all probiotic strains may survive in sufficient quantities to make it down to the gut microbiome and, even if the probiotic bacteria reach the gut microbiome, it may not last as long or have the same effect in each individual.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, human probiotics have often shown only limited microbiota modulation ability [16,28,35]. This resilience of the gut microbiota seems to depend on the basal microbiota composition, which may determine the responder or non-responder phenotype towards probiotic intervention in elderly [36].…”
Section: Discussionmentioning
confidence: 99%
“…Using fecal microbiota analysis at baseline and after dietary interventions, they were able to predict responsiveness of the host microbiota using microbial biomarkers [48]. Another human study profiling geriatric individuals revealed potential microbial biomarkers between probiotic respondents and non-respondents [49]. It was previously suggested that level of response depended on change in cholesterol; instead, the fecal microbiota provided a more clinically useful biomarker [49].…”
Section: Future Of Probiotic Designmentioning
confidence: 99%
“…Another human study profiling geriatric individuals revealed potential microbial biomarkers between probiotic respondents and non-respondents [49]. It was previously suggested that level of response depended on change in cholesterol; instead, the fecal microbiota provided a more clinically useful biomarker [49]. It is also important to note that the geriatric study identified a microbiota shift in non-respondents [49]; thus, it is pertinent to distinguish individuals that respond or do not respond to dietary interventions such as probiotics.…”
Section: Future Of Probiotic Designmentioning
confidence: 99%